Improving MSME Performance in Mojokerto City: Contribution of Digital Payment Convenience, Accounting Understanding and Business Experience - Sudarto, Triadi Agung; Juliardi, Dodik (International Journal of Business, Law, and Education, 2025)
MSMEs need to implement a digital payment strategy to make it easier for customers to transact online, allowing for quick payments that can be made in a short time, thereby becoming more effective and efficient. With digital payments, communication, and transactions can be done at any time and accessed from anywhere, thus providing ease of communication for business actors and consumers. Some strategies that MSMEs can employ to maintain their business include having an understanding of accounting, which enables them to track the flow of funds, expenditures, and income. Business actors are also better off having business experience, as this enables them to analyse MSMEs properly, as they are based on previous business experience. In addition to understanding accounting, the business experience of MSME actors is also no less important. The business experience of MSME actors is a key characteristic that can significantly impact the success of their businesses. Experienced MSME actors can overcome the problems that arise when conducting business. Entrepreneurs who have business experience will be more confident in running a business. This study aims to obtain information on how much 1) Understanding of accounting contributes significantly positively to the performance of MSMEs in Mojokerto City; 2) Business experience contributes significantly positively to the performance of MSMEs in Mojokerto City, and 3) The ease of digital payment contributes significantly positively to the performance of MSMEs in Mojokerto City. This type of research uses a quantitative method with an associative design. The population and sample in this study comprise MSME actors in Mojokerto City who are registered with the Mojokerto City Cooperatives and Micro Enterprises Office. The results of the study show that the ease of digital payment (X1) has a significant positive effect on the performance of MSMEs in Mojokerto City (Y), accounting understanding (X2) has no effect on the performance of MSMEs in Mojokerto City (Y), business experience (X3) has no effect on the performance of MSMEs in Mojokerto City (Y).